2021
DOI: 10.1007/s10803-021-05194-3
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Specificity of Interpersonal Synchrony Deficits to Autism Spectrum Disorder and Its Potential for Digitally Assisted Diagnostics

Abstract: Reliably diagnosing autism spectrum disorders (ASD) in adulthood poses a challenge to clinicians due to the absence of specific diagnostic markers. This study investigated the potential of interpersonal synchrony (IPS), which has been found to be reduced in ASD, to augment the diagnostic process. IPS was objectively assessed in videos of diagnostic interviews in a representative referral population from two specialized autism outpatient clinics. In contrast to the current screening tools that could not reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 49 publications
4
45
0
Order By: Relevance
“…The German versions of the following questionnaires where administrated: a demographic questionnaire, to collect biographical data and previous VR experience; the Multiple Choice Vocabulary Intelligence Test (verbal intelligence; MWT-B; [39]) and the Basic Intelligence Scale Scale 2 -Revision (non-verbal intelligence; CFT-20-R; [67]) to corroborate inclusion criteria of the participants' IQ; the Landolt C test, the Stereo Optical test [51] and the Ishihara colour-blindness test [12] for ocular and colour deficiencies. In phase three, after the VR task, participants were asked to answer a rapport questionnaire to assess the quality of the interaction with the avatar [35]; the autism-spectrumquotient (measuring extent of autistic traits; AQ, [8]) and the empathy quotient (to assess empathy; EQ, [7]). In addition, we measured motor difficulties with the Adult Dyspraxia Checklist (ADC) [33] and depressive symptoms with the Beck Depression Inventary (BDI-II) [27].…”
Section: Methodsmentioning
confidence: 99%
“…The German versions of the following questionnaires where administrated: a demographic questionnaire, to collect biographical data and previous VR experience; the Multiple Choice Vocabulary Intelligence Test (verbal intelligence; MWT-B; [39]) and the Basic Intelligence Scale Scale 2 -Revision (non-verbal intelligence; CFT-20-R; [67]) to corroborate inclusion criteria of the participants' IQ; the Landolt C test, the Stereo Optical test [51] and the Ishihara colour-blindness test [12] for ocular and colour deficiencies. In phase three, after the VR task, participants were asked to answer a rapport questionnaire to assess the quality of the interaction with the avatar [35]; the autism-spectrumquotient (measuring extent of autistic traits; AQ, [8]) and the empathy quotient (to assess empathy; EQ, [7]). In addition, we measured motor difficulties with the Adult Dyspraxia Checklist (ADC) [33] and depressive symptoms with the Beck Depression Inventary (BDI-II) [27].…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, autistic and non-autistic participants achieved comparable levels of synchrony in an interaction in which the social, perceptual, and motoric content of the interaction was substantially reduced, in that it involved only the exchange of signals with an unseen partner via a computer button press ( Koehne et al, 2016 ). Together with evidence that synchrony is reduced but still present at above chance levels in more complex interactions ( Georgescu et al, 2020 ; Koehler et al, 2021 ), this finding suggests that a basic tendency to synchronise may be intact in autism. However, it is unclear which particular processes may account for the differences in IS during naturalistic social interactions.…”
Section: Part 2 – Interpersonal Synchrony In Autismmentioning
confidence: 66%
“…Further, while there is some evidence of a positive association between motor abilities, assessed in an individual context, and IS ( Brezis et al, 2017 ), the existence of such an association has also been found to depend on the particular tasks used ( Fitzpatrick et al, 2017a ). Other studies have failed to find a significant association between motor abilities assessed in a solo context and IS in autism ( Kaur et al, 2018 ; Koehler et al, 2021 ). However, these studies used generalised measures of motor ability, rather than specific component processes of motor functioning ( Gowen and Hamilton, 2013 ), such as motor planning, motor timing, and motor control.…”
Section: Part 2 – Interpersonal Synchrony In Autismmentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, with this paper, we tested MEA's usability in dynamic full-body interactions between a facilitator and an autistic child where we investigate MEA's advantages and limitations in semi-experimental settings. MEA has been used in the last decade to measure interactional synchrony in research related to autism [53,54]. It is built on two distinct modules: 1) MEA which allows the computation of movement from video pixel changes and 2) the rMEA R package [8], which makes available the computation of synchrony from that pixel quantification data using windowed cross-correlation.…”
Section: 21mentioning
confidence: 99%